Pathomorphological examination of specimen after vacuum-assisted biopsy in patients with breast cancer after neoadjuvant systemic therapy - N. S. Amirov; A. S. Artemyeva; P. V. Krivorotko; V. V. Mortada; V. O. Smirnova; A. S. Emelyanov; R. S. Pesotskiy; S. S. Yerechshenko; E. K. Zhiltsova; T. T. Tabagua; Ya. I. Bondarchuk; D. A. Enaldieva; et al. (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Vacuum-assisted biopsy (VAB) of the tumor bed in the breast has shown promising results as a minimally invasive method for determining pCR. A significant disadvantage of VAB is the fragmentation of the obtained material and the lack of methods for determining generally accepted predictive and prognostic factors.The objective was to provide a description of the accumulated experience of histological examination of specimens obtained using VAB in patients with breast cancer after neoadjuvant systemic therapy.Methods and materials. A single-center, prospective, non-randomized study included patients with unifocal breast cancer (cT1–2N0–1M0). Patients who achieved a complete clinical response (cCR) underwent VAB. Based on the results of histological examination, patients without signs of residual tumor (pCR, ypT0N0) did not undergo further surgical intervention. When residual tumor cells (ypTisN0-1, ypT1-2N0-1) were detected, standard breast surgery was performed.Results. 35 patients with a mean age of 48.3 (31–67) years were included in the analysis. The examination of VAB samples showed that 11 (31.4 %) patients had a residual tumor, and in 24 (68.6 %) patients, no tumor cells were detected (ypT0N0). According to the Miller-Payne system, 28 patients had a complete pathological response, which corresponds to Miller-Payne=5 and pathological stage ypT0/ypTis (24 patients ypT0N0, 3 patients ypTisN0 and 1 patient ypT0N1). In 3 patients with residual invasive tumor, the tumor response according to the Miller-Payne scale corresponded to grade 3. There was a statistically significant correlation between presence of residual tumor cells in the outer counter after VAB and presence of residual tumor cells in the postoperative histology after standard surgery (Х2 p=0.01, Fisher exact test p=0.048). In addition, there was a statistically significant correlation between hormone receptor status and the degree of tumor response when evaluated using the Pearson criterion (p=0.046). We observed the smallest discordance between the data of the control examination and the data of the histological conclusion when interpreting the results of mammolymphoscintigraphy (25 %) and if 3 out of 3 studies described a complete clinical regression (16.7%).Conclusions. The method used to evaluate histological material allows to obtain predictive and prognostic information necessary to clarify further treatment tactics in accordance with modern standards. It is necessary to conduct more largescale studies in this area to answer the question if this method can be used in routine clinical practice.